Effect of preoperative anxiety on recovery time in general anesthesia - Taher, Abu; Salim Moral, M.; Ahamed, Mohammad S.; Hassnul Alam, M.; Siddique, Abul Bashar M.; Harun-Ur-Rashid, M. (International Journal of Research in Medical Sciences, 2025)
Background: Preoperative anxiety, common in patients undergoing surgery under general anesthesia, can negatively affect recovery by increasing stress responses and postoperative complications. This study investigates the impact of preoperative anxiety on recovery times and evaluates the effectiveness of non-pharmacological interventions, like relaxation techniques and patient education, in reducing anxiety and improving surgical outcomes. The aim was to assess the impact of preoperative anxiety on recovery time and evaluate anxiety management strategies in surgical patients. Methods: This prospective observational study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from June 2022 to May 2023, with 142 patients aged 20-60 years undergoing elective surgery under general anesthesia. Data collection included demographics, preoperative anxiety using the state-trait anxiety inventory (STAI), physiological stress indicators, and recovery times. Patients with psychiatric conditions or on anxiety medications were excluded. Statistical analysis was performed using statistical package for the social sciences (SPSS) (version 27.0.1) to assess anxiety and recovery outcomes. Results: The largest group of patients was aged 40-49 (29.58%) with more males (54.93%). Moderate preoperative anxiety was most common (38.73%). Surgery typically lasted 2-3 hours (38.73%), and most patients recovered within 3-4 hours (36.62%). Mild anxiety patients had faster recovery times, while severe anxiety prolonged recovery. Pain was the most frequent postoperative complication (38.73%), followed by nausea/vomiting (31.69%) and drowsiness (21.13%). Conclusions: Preoperative anxiety prolongs recovery time. Effective management through pharmacological and non-pharmacological methods enhances postoperative recovery and outcomes.